Channels of resistance: global television and local empowerment - Dowmunt, Tony (BFI Publishing in association with Channel Four Television, 1993)
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Océanie (corpus analysé); 4-Europe (lieu de production du savoir); Angleterre (lieu de production du savoir); Australie (corpus analysé); Brésil (corpus analysé); Canada (corpus analysé)

Sovereign Words: Indigenous Art, Curation and Criticism - García-Antón, Katya (Office for Contemporary Art Norway, 2018)
Artists and cultural practitioners from Indigenous communities around the world are increasingly in the international spotlight. As museums and curators race to consider the planetary reach of their art collections and exhibitions, this publication draws upon the challenges faced today by cultural workers, Indigenous and non-Indigenous, to engage meaningfully and ethically with the histories, presents and futures of Indigenous cultural practices and world-views. Sixteen Indigenous voices convene to consider some of the most burning questions surrounding this field. How will novel methodologies of word/voice-crafting be constituted to empower the Indigenous discourses of the future? Is it sufficient to expand the Modernist art-historical canon through the politics of inclusion? Is this expansion a new form of colonisation, or does it foster the cosmopolitan thought that Indigenous communities have always inhabited? To whom does the much talked-of 'Indigenous Turn' belong? Does it represent a hegemonic project of introspection and revision in the face of today's ecocidal, genocidal and existential crises?"–Page 4 de la couverture. Autres auteurs/titres:edited by Katya García-Antón ; contributors, Daniel Browning, Kabita Chakma, Megan Cope, Santosh Kumar Das, Hannah Donnelly, Léuli Māzyār Luna'i Eshrāghi, David Garneau, Biung Ismahasan, Kimberley Moulton, Máret Ánne Sara, Venkat Raman Singh Shyam, Irene Snarby, Ánde Somby, Megan Tamati-Quennell, Prashanta Tripura, Sontosh Bikash Tripura.
Section: 287 pages : illustrations (principalement en couleur) ; 24 cm.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Artistes femmes, queer et autochtones face à leur(s) image(s): pour une histoire intersectionnelle et décoloniale des arts contemporains autochtones aux Etats-Unis et au Canada (1969-2019) - Journée, Aurélie (École des hautes études en sciences sociales, 2020)
Fin des années 1960 aux Etats-Unis, les Indians of All Tribes impulsent un mouvement de contestations sociales qui a pour but la reconnaissance des droits inhérents aux peuples autochtones à la souveraineté et à l'auto-détermination. L'American Indian Movement et sa branche féminine Women of All Red Nations s'emparent de ces questions sociales, politiques et culturelles. Femmes et hommes entament de concert un processus d'émancipation dont l'accomplissement ne cesse d'être repoussé par les politiques assimilatrices successives du gouvernement états-unien. Au Canada aussi, des mobilisations collectives éclatent dans les années 1980 et 1990, et culminent avec les événements de Restigouche (1984) et la Crise d'Oka (1990). Ces évènements majeurs inspirent toute une jeune génération d'artistes autochtones et de femmes en particulier, formées notamment à l'Institute of American Indian Arts à Santa Fe (Nouveau-Mexique). De formations universitaires approfondies, elles développent des démarches artistiques transdisciplinaires à mi-chemin entre l'histoire de l'art et l'ethnographie. Elles mettent en évidence la porosité et la friabilité des frontières instaurées dans tous les secteurs par la société dominante contre les groupes considérés comme minoritaires. A cette fin, le photographique - par lequel nous désignons la pratique, la technique et l'image photographiques - devient un outil stratégique majeur de réappropriation et de réaffirmation de ce qu'elles sont et tendent à incarner. Ces artistes femmes interrogent grâce à ce médium les façons dont elles ont été représentées et se représentent elles-mêmes dans le cadre de démarches critiques des stéréotypes dont elles font l'objet depuis plusieurs siècles d'appropriation culturelle. Elles repensent par ce biais leurs identités, les rapports qu'elles entretiennent à leurs corps, à leurs sexualités et à leurs genres, à l'aune de leurs propres spiritualités. Grâce à leurs images artistiques et politiques, fruits de pratiques fondées sur une analogie entre la violation de leurs droits, l'exploitation de leurs terres et territoires, et les violences sexuelles dont elles font l'objet, elles continuent à prendre part aux mouvements de résistance actuels qui s'opposent aux projets extractivistes face auxquels elles s'affirment, une nouvelle fois, en première ligne. A partir d'un corpus iconographique de près de 400 œuvres réalisées entre 1969 et 2019, et d'entretiens individuels avec des artistes et des militantes femmes et queer autochtones des Etats-Unis et du Canada, cette thèse a pour objectif de montrer en quoi ces images - en particulier photographiques configurent des épistémologies nouvelles dans une perspective intersectionnelle, décoloniale et anticapitaliste, et s'inscrivent dans la continuité d'un processus de réaffirmation des droits inhérents des peuples autochtones, garantis par la Déclaration des Nations Unies sur les Droits des Peuples Autochtones (2007)
Pages: 1 online resource
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Decolonial Pedagogy: Examining Sites of Resistance, Resurgence, and Renewal - Wane, Njoki Nathani; Todd, Kimberly L (Palgrave Macmillan, 2018)
"Through innovative and critical research, this anthology inquires and challenges issues of race and positionality, empirical sciences, colonial education models, and indigenous knowledges. Chapter authors from diverse backgrounds present empirical explorations that examine how decolonial work and Indigenous knowledges disrupt, problematize, challenge, and transform ongoing colonial oppression and colonial paradigm. This book utilizes provocative and critical research that takes up issues of race, the shortfalls of empirical sciences, colonial education models, and the need for a resurgence in Indigenous knowledges to usher in a new public sphere. This book is a testament of hope that places decolonization at the heart of our human community." – Prové de l'editor.
OCLC: 1139473230
Keywords: 1-Histoire de l'art; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice noir.e; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Towards Sovereign Games - LaPensée, Elizabeth A.; Laiti, Outi; Longboat, Maize (Games and Culture, 2021)
Video games can be dynamic sovereign spaces for Indigenous representation and expression when the self-determination of Indigenous people is supported. Where ga...
Publisher: SAGE PublicationsSage CA: Los Angeles, CA
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

The Routledge Companion to Media and Race - Campbell, Christopher (Routledge, 2017)
"The Routledge Companion to Media and Race serves as a comprehensive guide for scholars, students, and media professionals who seek to understand the key debates about the impact of media messages on racial attitudes and understanding. Broad in scope and richly presented from a diversity of perspectives, the book is divided into three sections: first, it summarizes the theoretical approaches that scholars have adopted to analyze the complexities of media messages about race and ethnicity, from the notion of 'representation' to more recent concepts like Critical Race Theory. Second, the book reviews studies related to a variety of media, including film, television, print media, social media, music, and video games. Finally, contributors present a broad summary of media issues related to specific races and ethnicities and describe the relationship of the study of race to the study of gender and sexuality"–Provided by publisher.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art; _À vérifier-Télé

Never Alone. A study of Articulations of Indigenous Religion in the Video Game - Lohne, Inger Lise Damli (UiT Norges arktiske universitet, 2020)
This thesis explores the many ways indigenous religion is articulated, performed and translated in the video game Never Alone - Kisima Inŋitchuŋa (2014). The video game was among the first of its kind – being made in a close collaboration with an indigenous group, and published by the first indigenous owned video game company in the U.S.A. At launch, Never Alone gathered attention from traditional media in both North America and in Europe, and the game reached a global audience. Never Alone tells a story based on Inupiat storytelling, and Cultural Ambassadors gives the player an insight into Inupiat culture and tradition. Never Alone balances on the edge between the conventions of the video game medium and its genres, and of indigenous tradition and religion. This thesis examines how vocabularies that can be related to ‘indigenous religion’ are used and translated in Never Alone, and how these vocabularies relate to a globalizing discourse on indigenous religion. This thesis also explores how the medium of video games facilitates new ways of reclaiming traditions and articulating indigenous religion.
Accepted: 2020-12-18T09:22:21Z
Keywords: 1-Jeux vidéo; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Europe (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

Playing with the Past: Digital Games and the Simulation of History - Kapell, Matthew Wilhelm; Elliott, Andrew B. R. (Bloomsbury Publishing USA, 2013)
Game Studies is a rapidly growing area of contemporary scholarship, yet volumes in the area have tended to focus on more general issues. With Playing with the Past, game studies is taken to the next level by offering a specific and detailed analysis of one area of digital game play – the representation of history. The collection focuses on the ways in which gamers engage with, play with, recreate, subvert, reverse and direct the historical past, and what effect this has on the ways in which we go about constructing the present or imagining a future. What can World War Two strategy games teach us about the reality of this complex and multifaceted period? Do the possibilities of playing with the past change the way we understand history? If we embody a colonialist's perspective to conquer 'primitive' tribes in Colonization, does this privilege a distinct way of viewing history as benevolent intervention over imperialist expansion? The fusion of these two fields allows the editors to pose new questions about the ways in which gamers interact with their game worlds. Drawing these threads together, the collection concludes by asking whether digital games - which represent history or historical change - alter the way we, today, understand history itself.
Google-Books-ID: jXjHAgAAQBAJ
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé